Interdisciplinary Innovations in the Management of Pediatric Mandibular Fractures: Integrating Dental, Radiological, and Nursing Perspectives - Alenizi, Dhabha Dauod; Dalal Nasser Alharbi; Ashwaq Mohammed Haddadi; Aeshah Ali Salem Albalawi; Bayan Ahmed Mabrook Alkhred; Ali Humood Salah Alharbi; Mohammed Yahya Alfifi; Jawaher Homoud Alanazi; Abdulrahman Saad Bijad Alsubaie; Mohammed Ayad Al Harbi; et al. (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Pediatric mandibular fractures present unique challenges due to the presence of developing tooth buds, evolving occlusion, and the dynamic growth potential of the jaw. Management must balance achieving stable fixation with preserving long-term growth and function, necessitating a departure from standard adult protocols. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This article aims to present and evaluate a conservative, interdisciplinary approach to managing pediatric mandibular fractures, focusing on techniques that minimize iatrogenic harm to dental and growth structures while ensuring effective healing. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> The methods are illustrated through a series of case studies (ages 1.5 to 16 years) involving mandibular fractures. The primary technique involved closed reduction using a custom-molded impression compound splint secured with circummandibular wiring, often combined with bridle wiring for concomitant dental injuries. This approach is contrasted with other methods like intermaxillary fixation (IMF) with interdental hooks in older children. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> The presented technique proved highly effective across all cases. It provided stable, non-rigid fixation, achieved satisfactory fracture alignment, and facilitated uncomplicated healing. Key outcomes included the restoration of normal occlusion, rapid return to function, and the absence of complications such as infection or injury to tooth buds. The method was also noted for its procedural efficiency, cost-effectiveness, and ease of removal. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A conservative strategy utilizing impression compound splints and circummandibular wiring is a safe, reliable, and biologically sound option for pediatric mandibular fracture management. Its success underscores the critical importance of an interdisciplinary team integrating dental, surgical, radiological, and nursing expertise to optimize outcomes for the growing patient.